Pengaruh Generasi Milenial Terhadap Percepatan Tranformasi Digital di Industri Perdangangan - Dian Sudianti; Naufal Khairiansyah; Willy Jovadi Wijaya; Ayu Nurjanah M Candra; Selliatun Nuriah (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Â The influence of Millennials in driving digital transformation in the commercial sector. Through surveys and data analysis, this research examines how Millennials who grew up in the digital era influence technology change and adoption in the business sector. The results show that the Millennial generation can have a positive impact on the industry's digital transformation process. They tend to be more open to technological innovation, are highly digitally literate, and can influence businesses to adopt more effective digital solutions.The importance of this research is to understand the role of the millennial generation in digital transformation in the trading industry, as well as how businesses can utilize it to increase competitiveness in the digital era. The influence of the Millennial generation to drive digital transformation in the trading industry lies in the fact that they are instrumental to driving digital transformation in the industry. They are generally more familiar with digital technologies and innovations, which are changing the way businesses operate, including the use of e-commerce, social media, and other technical solutions.. As a result, Millennials have accelerated the adoption of digital technologies in commerce, helping businesses operate more efficiently, connect with customers and compete in the digital age.